Comparison between different methods diagnostic Enterocoocus species (Journal of the College of Basic Education, 2022)
One hindered and five isolates of Enterococcus species were identification from 705 samples of urine collected from UTI patient in Baghdad from period between February - may 2014. Azide blood agar and esculin media were used for preliminary identification of Enterococcus while chromogenic agar orientation medium as used as confirmatory media for this paper modification media showed that 55 isolates of Enterococcus were Enterococcus faecalis and 50 isolates were Enterococcus faecium.PCR technique using ddlE.faecalis and ddl E.faecium proved that all isolates of E.faecalis and E.faecium previously identification successfully procedure PCR amplification product i.e. conform the previously diagnosis